Microwave‐assisted acid hydrolysis for whole‐bone proteomics and paleoproteomics. (10th January 2020) - Colleary, Caitlin; Little, Nicole C.; Cleland, Timothy P.
Abstract : Rationale: Whole‐bone proteomic analyses rely on lengthy sample preparation including demineralization and digestion to break bone down into peptides to recover using mass spectrometry. However, microwave‐assisted acid hydrolysis, a technique used in proteomic analyses of other soft tissues and cells, will combine both demineralization and digestion and only take minutes. Methods: To test microwave‐assisted hydrolysis on whole moose bone, we microwaved five concentrations of acetic and formic acids (15%, 12.5%, 10%, 7.5% and 5%) for three times (10, 20 and 30 min) at 140°C using an ETHOS UP high performance microwave digestion system. Peptides were injected and separated using Thermo BioBasic C18 columns and detected with an LTQ Orbitrap Velos mass spectrometer. We searched the raw data on PEAKS 8.5 against the white‐tailed deer database. Results: Formic acid hydrolysis led to the most complete digestion, and therefore the highest number of peptide spectrum matches, more protein groups and better sequence coverage for collagenous proteins. However, for the formic acid samples there is a tradeoff with digestion completeness and a higher incidence of in vitro modifications (i.e. formylation) that are not induced using acetic acid. Acetic acid has greater cleavage specificity and higher sequence coverage for non‐collagenous proteins. Conclusions: Depending on the goals of analysis, there are benefits and drawbacks to using both acetic acid and formic acid. Overall, microwave‐assisted acid hydrolysis was successful in demineralizing and digesting bone fragments to considerably speed up the preparation for bottom‐up proteomics analysis.